Sigmoid Volvulus Sebagai Salah Satu Penyebab Terjadinya Ileus Obstruksi - Asri Aprillya; Haris Setia Ampera Hutagaol (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Sigmoid volvulus is an event in which a part of the intestine is twisted around the blood supply. This incident usually occurs in endemic areas which account for 13% to 42% of all intestinal disorders. The condition is most common in patients over 60 years of age and along with several risk factors. Presents with colic abdominal pain, nausea, vomiting, and constipation; Usually there is abdominal distension, tenderness with varying degrees. On plain radiography, the key to diagnosing sigmoid volvulus is the "Coffee Bean" sign formed in the center of the image. The management that can be given in this case can be in the form of non-surgical and surgical depending on the severity of the patient's disease.